Internal Control System in Goa Medical College and Hospital (1999-2004) - CAG of India (CAG of India, 2005)
The Goa Medical College and Hospital (GMCH) was established in 1842. It has a bed strength of 1000 in the main hospital at Bambolim, 80 beds at the TB Hospital at St. Inez and 20 beds at the Rural Health Centre, Mandur. A review of the internal controls in GMCH revealed that despite being the only Medical Training Institute in the State, the College and the attached hospitals did not have any Administration Manual of its own. There were huge savings under capital budget indicating weak budgetary control. Internal audit of the GMCH had not been carried out by the Director of Accounts. Some of the important deficiencies in financial and administrative controls are highlighted below. 1. There were savings in capital budget ranging from 15 to 55 percent during 1999-2004, due to weak budgetary control. 2. Receipts from patients in private wards were utilised for refunds without routing it through cash book and patients were discharged without recovery of hospital charges. 3. Stock account of receipt books received from Government Printing Press was not maintained by the Medical Records Section of GMCH. Twelve unnumbered receipt books were missing from the stock of Accounts Section. 4. Oxygen outlets installed at a cost of Rs. 8.59 lakh in two departments of GMCH were not put to use due to defective system of maintenance and upkeep of equipment. 5. The GMCH recruited contract labour for sweeping and security services in excess of the sanctioned strength. A sweeping contract was also extended irregularly. There were weaknesses in financial control on payment released to contract labour. 6. Unserviceable articles/equipment with purchase value of Rs. 65.90 lakh were lying undisposed. 7. System of internal audit was non existent in GMCH.
For the Period 1999-2000 to 2003-04